Exclusion of the alpha 1(II) cartilage collagen gene as the mutant locus in type IA osteogenesis imperfecta. Issue 3 (June 1985) - Sykes, B; Smith, R; Vipond, S; Paterson, C; Cheah, K; Solomon, E
Abstract : Using two restriction site polymorphisms within the structural gene coding for human type II collagen we have examined the segregation of this gene in three pedigrees with dominantly inherited osteogenesis imperfecta (Sillence type IA). We have demonstrated that the gene does not segregate with clinical expression of the disease and cannot, therefore, contain the mutation responsible for osteogenesis imperfecta in these families.